2010
DOI: 10.1271/bbb.90712
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Hydrostatic Pressure Treatment on the Flavor and Color of Grated Ginger

Abstract: High hydrostatic pressure (HHP) was applied to grated ginger in order to inactivate quality-degrading enzymes in a non-thermal manner. The effects of HHP treatment on the flavor and the color of the grated ginger were investigated just after treatment and during storage. After HHP treatment (400 MPa, 5 min), geraniol dehydrogenase (GeDH) was inactivated to less than 5%, but the activity of polyphenol oxidase (PPO) was reduced only to 37%. Heat treatment (100 °C, 10 min) inactivated GeDH to 43% and PPO to about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It was also observed that the neral content decreased, while the geranial content increased after HHP and UHT treatments. This could be attributed to the isomerization induced by HHP and high temperature treatments, according to a study by Yamaguchi et al (2010). Connell (1970) reported that fresh ginger rhizomes possessed a Bcitrus-like^aroma, which are the contributing compounds being identified as geranial and neral.…”
Section: Volatile Aroma Compositionmentioning
confidence: 99%
“…It was also observed that the neral content decreased, while the geranial content increased after HHP and UHT treatments. This could be attributed to the isomerization induced by HHP and high temperature treatments, according to a study by Yamaguchi et al (2010). Connell (1970) reported that fresh ginger rhizomes possessed a Bcitrus-like^aroma, which are the contributing compounds being identified as geranial and neral.…”
Section: Volatile Aroma Compositionmentioning
confidence: 99%
“…In addition, even though thermal treatment is very effective to avoid enzymatic browning, it is the reason of changes in the appearance, texture, color, and flavor of food products (Queiroz, Lopes, Fialho, & Valente-Mesquita, 2008). So, nonthermal treatment is needed as a substitute to keep the fresh-like color, and texture of fresh-cut fruits and vegetables (Rico, Martín-Diana, Barat, & Barry-Ryan, 2007) as well as effective on enzyme inactivation such as HHP reduces the PPO activity (37%) in ginger (Yamaguchi, Kato, Noma, Igura, & Shimoda, 2010), total inhibition of browning enzymes in apple after PEF treatment (Schilling et al, 2008), complete inactivation of different enzymes after thermo-sonication treatment in grapefruit juice (Aadil, Wang, et al, 2015;Aadil, Zeng, Zhang, et al, 2015b). The mechanism behind the inactivation of enzymes could be the proper utilization of temperature, frequency, processing time, and the food matrix (Fan, Zhang, & Jiang, 2019;Jang & Moon, 2011;Roobab, Aadil, Madni, & Bekhit, 2018;Sun, Zhong, Cao, Lin, & Ye, 2015).…”
mentioning
confidence: 99%
“…In addition to drying, in some studies the process of heating the ginger rhizomes was used, and this method’s influence on the content of individual ginger compounds in the rhizome was investigated. From the results of Yamaguchi et al (2010) [ 63 ], it can be concluded that the heat treatment of ginger in a thermostated water bath at 100 °C for 10 min had a positive effect on the volatile component profile of ginger. After the heat treatment, an increase in the concentration of 22 aromatic compounds was observed, whereas the concentration of only 9 compounds decreased.…”
Section: Food Processing Of Ginger Rhizomesmentioning
confidence: 99%